THE ROLE OF WEBSITES IN COMMUNICATING CSR POLICY BY PUBLIC COMPANIES LISTED ON THE WARSAW STOCK EXCHANGE (Polityki Europejskie, Finanse i Marketing)
Companies, by engaging in Corporate Social Responsibility (CSR) activities, can generate favorable stakeholder behaviors and build up their corporate reputations. On the other hand, stakeholders’ low awareness of these activities, and their lack of confidence in corporations, create major obstacles in gaining maximum benefits for these companies. This gives rise to a need for effective CSR communication. The purpose of the research presented in this paper was to identify how companies listed on the Warsaw Stock Exchange use their websites to communicate CSR activities. The research was based on the analysis of company documents. The main results show that company size was the most important factor differentiating CSR communication.